Competitiveness of the BRICS Countries on the Field of International Higher Education - Anita Veres (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The aim of this study is to examine the higher education of BRICS (Brazil, Russia, India, China and South Africa) countries from the perspective of international student mobility and international competitiveness. The WEF-GCI, the UNESCO and the QS database provided data for the analysis. The extracted data were analyzed using descriptive statistical comparative and time series analysis methods. The study reveals the strengths and weaknesses of the higher education systems of the BRICS countries. The higher education of this group of countries could not be considered homogeneous. Brazil, China and South Africa are the strongest on the subfield of academic reputation, Brazil and China in the employer reputation, India in the citations per faculty while Russia in the faculty-to-student ratio and reception of students outside of the country. However, internationalization in general is a strategic area that needs improvement in all these countries. The goal of this research is to give a brief summary of the position of the BRICS countries in the field of international student mobility
Keywords: I21; I25; F60; 330; BRICS; higher education; competiveness; ranking; development; society